Front Cover: Nonaqueous capillary electrophoresis mass spectrometry method for determining highly hydrophobic peptides. Issue 9 (May 2018) - Cheng, Jianhui; Chen, David D. Y.
Abstract : DOI:10.1002/elps.201700364 The cover picture shows that temporin peptides originally derived from Rana temporaria can be analysed by a well‐developed non‐aqueous capillary electrophoresis–mass spectrometry (NACE–MS) method. The structure of Temporin A, one of the analytes, is shown in this picture. The structure shows that most of the side chains in this sequence are hydrophobic. Temporins' high hydrophobicity makes it difficult to analyse it using traditional aqueous capillary electrophoresis. In this study, it is shown that NACE is capable of dealing with hydrophobic analytes.